Antigenic specificity of chlorpromazine-induced antinuclear antibodies - Alarcón-Segovia, D. (1973)
A few patients have been reported who developed systemic lupus erythematosus (SLE) in the course of prolonged treatment with chlorpromazine. Patients on this drug have also been found to have antinuclear antibodies (ANAs) although they do not develop lupus. We have studied the antigenic specificity of ANAs in fifty-four patients on longterm chlorpromazine treatment and compared our findings with those on 175 patients on anticonvulsants, 215 patients on isoniazid, 109 SLE patients and fifty-four healthy subjects, sex and age matched to the chlorpromazine patients. Thirty-nine per cent of patients on chlorpromazine had ANAs which were most frequently directed to single stranded (s)DNA. In contrast, patients on anticonvulsants as well as those on isoniazid had ANA directed to soluble nucleoprotein (sNP) most frequently and none of the patients on isoniazid had ANA to sDNA. The mechanisms by which chlorpromazine, isoniazid or anticonvulsant intake results in ANAs probably differ. Our findings suggest that development of ANAs in patients on chlorpromazine may be initiated by interaction of the drug with denatured DNA.